2019
DOI: 10.48550/arxiv.1910.09752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Charge Density Waves on a Half-Filled Decorated Honeycomb Lattice

Chunhan Feng,
Huaiming Guo,
Richard T. Scalettar

Abstract: Tight binding models like the Hubbard Hamiltonian are most often explored in the context of uniform intersite hopping t. The electron-electron interactions, if sufficiently large compared to this translationally invariant t, can give rise to ordered magnetic phases and Mott insulator transitions, especially at commensurate filling. The more complex situation of non-uniform t has been studied within a number of situations, perhaps most prominently in multi-band geometries where there is a natural distinction of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…(The order parameter has a continuous symmetry.) A recent study [30] has shown that ω 0 10 2 t is required to achieve the −U Hubbard model limit, a surprisingly large value.…”
Section: Existence Of Long Range Cdw Ordermentioning
confidence: 99%
“…(The order parameter has a continuous symmetry.) A recent study [30] has shown that ω 0 10 2 t is required to achieve the −U Hubbard model limit, a surprisingly large value.…”
Section: Existence Of Long Range Cdw Ordermentioning
confidence: 99%